Acoustic Emission as a Method for Analyzing Changes and Detecting Damage in Composite Materials During Loading - PANASIUK, Katarzyna; DUDZIK, Krzysztof; HAJDUKIEWICZ, Grzegorz (Archives of Acoustics, 2021)
Thanks to their excellent strength and durability, composite materials are used to manufacture many important structural elements. In the face of their extensive use, it is crucial to seek suitable methods for monitoring damages and locating their origins. The purpose of the article was to verify the possibility of applying the acoustic emissions (AE) method in the detection of damages in the structures of composite materials. The experimental part comprised static tensile tests carried out on various sandwich composites, including simultaneous registration of elastic waves with increasing loads, carried out with the use of an acousticelectrical sensor connected. The signal obtained from the sensor was then further processed and used to draw up diagrams of the AE hits, amplitude, root mean square of the AE source signal (RMS) and duration in the function of time. These diagrams were then applied on their corresponding stretching curves, the obtained charts were analysed. The results obtained point to a conclusion that the acoustic emissions method can be successfully used to detect and locate composite material damages.